Analysis of Activity-based Costing of Services for Drug Addicted Patients in Pattani Drug Dependence Treatment Center - ฮะ มัซตูรา; สิงห์ช่างชัย เพชรน้อย; ลิ้มชัยอรุณเรือง สาวิตรี (Journal of health and health management, 2015)
This descriptive research aimed to analyze the cost of service activities for drug addicts in Pattani Drug Dependence Treatment Center, Pattani Province, by studying 206 drug addicts with drug dependence in in-patient department. Data were collected during 3 months from 2 sources: primary sources consisted of an information questionnaire, a number of activities and time in service activities, and secondary sources consisted of payment bill and doctor order sheets, which were validated by 5 experts (CVI=1.00). Data were analyzed using number, percentage, mean, standard deviation and descriptive statistics. The result of this research revealed that the total cost of in-patient services activities during 3 months was 1,913,833.70 baht for 206 patients. Top 3 of service activities costs were on the detoxification activities cost 905,344.03 baht (unit cost = 9290.45 baht), the treatment activities cost (47.31%), the rehabilitation activities cost 817,774.60 baht (42.73%), and the moving activities cost 97,697.16 baht (5.10%). Whereas, the lowest activities cost was financial in-patient activities cost 14,030.34 baht (0.73%). The total activities costs were high, because the people needed for these activities have to be professionals which comes with a high salary. In additive, the family should be supported to participate in treatment and to improve the effectiveness of drug dependence treatment and besides, the spread of drug in the community should be prevented to decrease the number of patients with drug dependence so the cost of drug dependence treatment would be reduced.